RT-qPCR and RT-Digital PCR: A Comparison of Different Platforms for the Evaluation of Residual Disease in Chronic Myeloid Leukemia. (6th January 2020) - Alikian, Mary; Whale, Alexandra S; Akiki, Susanna; Piechocki, Kim; Torrado, Celia; Myint, Thet; Cowen, Simon; Griffiths, Michael; Reid, Alistair G; Apperley, Jane; White, Helen; Huggett, Jim F; et al.
Abstract: BACKGROUND: Tyrosine kinase inhibitors (TKIs) are the cornerstone of successful clinical management of patients with chronic myeloid leukemia (CML). Quantitative monitoring of the percentage of the fusion transcript BCR-ABL1 (breakpoint cluster region–c-abl oncogene 1, non-receptor tyrosine kinase) BCR-ABL1 IS (% BCR-ABL1 IS ) by reverse transcription–quantitative PCR (RT-qPCR) is the gold standard strategy for evaluating patient response to TKIs and classification into prognostic subgroups. However, this approach can be challenging to perform in a reproducible manner. Reverse-transcription digital PCR (RT-dPCR) is an adaptation of this method that could provide the robust and standardized workflow needed for truly standardized patient stratification. METHODS: BCR-ABL1 and ABL1 transcript copy numbers were quantified in a total of 102 samples; 70 CML patients undergoing TKI therapy and 32 non-CML individuals. 3 commercially available digital PCR platforms (QS3D, QX200 and Raindrop) were compared with the platform routinely used in the clinic for RT-qPCR using the EAC (Europe Against Cancer) assay. RESULTS: Measurements on all instruments correlated well when the % BCR-ABL1 IS was ≥0.1%. In patients with residual disease below this level, greater variations were measured both within and between instruments limiting comparable performance to a 4 log dynamic range. CONCLUSIONS: RT-dPCR was able to quantify low-level BCR-ABL1 transcript copies but was unable to improve sensitivity below the level of detection achieved by RT-qPCR. However, RT-dPCR was able to perform these sensitive measurements without use of a calibration curve. Adaptions to the protocol to increase the amount of RNA measured are likely to be necessary to improve the analytical sensitivity of BCR-ABL testing on a dPCR platform.